Trust of inpatient physicians among parents of children with medical complexity: a qualitative study - Dewan, Tammie; Whiteley, Andrea; MacKay, Lyndsay Jerusha; Martens, Rachel; Noel, Melanie; Barnard, Chantelle; Jordan, Isabel; Janvier, Anne; Thorne, Sally (Frontiers in Pediatrics, 2024)
Trust is a foundation of the therapeutic relationship and is associated with important patient outcomes. Building trust between parents of children with medical complexity (CMC) and physicians during inpatient care is complicated by lack of relational continuity, cumulative (sometimes negative) parent experiences and the need to adjust roles and expectations to accommodate parental expertise. This study’s objective was to describe how parents of CMC conceptualize trust with physicians within the pediatric inpatient setting and to provide recommendations for building trust in these relationships. Qualitative semi-structured research interviews with parents of CMC were analyzed using interpretive description methodology. Researchers interviewed 16 parents of CMC. The research team identified one overarching meta theme regarding factors that influence trust development: situational awareness is needed to inform personalized care of children and families. There were also six major themes: 1) ensuring that the focus is on the child and family, 2) respecting both parent and physician expertise, 3) collaborating effectively, 4) maintaining a flow of communication, 5) acknowledging the impact of personal attributes, and 6) recognizing issues related to the healthcare system. Many elements that facilitated trust development were also components of patient- and family-centered care. Parents in this study approached trust with inpatient physicians as something that needs to be earned and reciprocated. To gain the trust of parents of CMC, inpatient physicians should personalize medical care to address the needs of each child and should explore the perceptions, expertise, and previous experiences of their parents.